Improving oral health in institutionalised elderly people by educating caregivers: a randomised controlled trial - Frenkel HF, Harvey I, Newcombe RG (Blackwell Synergy, 2001)
This cluster-randomised controlled trial assessed whether oral health care education (OHCE) for nursing home caregivers would achieve improvements in clients’ oral health.